Truncated vitronectin with E-cadherin enables the xeno-free derivation of human embryonic stem cells - Souralova, Tereza; Hulinova, Daniela; Jeseta, Michal; Ventruba, Pavel; Hampl, Ales; Koutna, Irena (Scientific reports, 2023)
Human embryonic stem cells (hESCs) have unique abilities that enable their use in cell therapy, disease modeling, and drug development. Their derivation is usually performed using a feeder layer, which is undefined and can potentially cause a contamination by xeno components, therefore there is a tendency to replace feeders with xeno-free defined substrates in recent years. Three hESC lines were successfully derived on the vitronectin with a truncated N-terminus (VTN-N) in combination with E-cadherin in xeno-free conditions for the first time, and their undifferentiated state, hESC morphology, and standard karyotypes together with their potential to differentiate into three germ layers were confirmed. These results support the conclusion that the VTN-N/E-cadherin is a suitable substrate for the xeno-free derivation of hESCs and can be used for the derivation of hESCs according to good manufacturing practices.
Keywords: Cadherins; obchod; buněčná a tkáňová terapie; Commerce; lidé; Cell- and Tissue-Based Therapy; lidské embryonální kmenové buňky; Vitronectin; Humans; Human Embryonic Stem Cells; kadheriny; vitronektin